Alternative nivolumab duration and scheduling in advanced nonsmall cell lung cancer: A real‐world evidence. Issue 5 (16th September 2020) - Dudnik, Elizabeth; Moskovitz, Mor; Agbarya, Abed; Gottfried, Teodor; Shochat, Tzippy; Urban, Damien; Zer, Alona; Rotem, Ofer; Moore, Assaf; Yust, Shlomit; Peled, Nir; Wollner, Mira; et al.
Abstract: In advanced nonsmall cell lung cancer (aNSCLC), stopping nivolumab after 12 months negatively affects outcomes. We performed a world data‐based analysis assessing the value of nivolumab continuation and optimal dosing beyond 24 months. Out of 697 consecutive patients with aNSCLC in whom nivolumab was initiated between 2015 and 2018, 45 patients receiving nivolumab for ≥24 months were selected. These were divided into Groups A: nivolumab administered at a dose 3 mg/kg q2 weeks/240 mg q2 weeks/480 mg q4 weeks, n = 25; B: nivolumab re‐scheduled to a nonstandard dose 3 mg/kg q3 weeks‐q8 weeks, n = 13; C: nivolumab stopped after 24 months, n = 7; (in Groups B and C—for reasons other than progressive disease or intolerable toxicity). Progression‐free survival (PFS) (Revised Response Evaluation Criteria in Solid Tumors, version 1.1) and safety (Common Terminology Criteria for Adverse Events, version 4.03) were assessed. With median follow‐up of 35.6 months (interquartile range 28.4‐41.8), 4%, 31%, 29% and 30% of patients progressed in Groups A, B, C and B+C, respectively. PFS at 36 months since nivolumab initiation comprised 100%, 67%, 67% and 67%, in Groups A, B, C and B+C, respectively. PFS at 40 months since nivolumab initiation comprised 83%, 67%, 67% and 67%, in Groups A, B, C and B+C, respectively. Allocation to Group A vs Group B, C and B+C was associated with hazard ratio for PFS‐0.20 (95% confidence interval [CI], 0.02‐1.77, P ‐.15), 0.20 (95% CI, 0.02‐2.25, P ‐.19) and 0.20 (95% CI, 0.02‐1.66, P ‐.14), respectively. No differences in newly occurring or worsening adverse events between the groups were observed. A trend for worse PFS was observed with alternative nivolumab scheduling or quitting 24 months after initiation. Continuing nivolumab at a standard dose until disease progression or intolerable toxicity remains the standard treatment option. Abstract : What's new? Optimal duration and schedule of immune check‐point inhibitors (ICPis) in advanced nonsmall cell lung cancer (aNSCLC) is unknown. In this retrospective analysis of aNSCLC patients treated with the ICPi nivolumab, alternative nivolumab scheduling and stopping nivolumab within 24 months of initiation were associated with a nonsignificant but strong trend toward worse progression‐free survival. Continuing nivolumab beyond 24 months was not associated with excessive toxicity. Although further investigation in a large patient population is needed, the findings suggest that standard use of nivolumab, until disease progression or toxicity force its discontinuation, remains the best treatment option for aNSCLC.